Pengaruh Celebrity Endorsement, Brand Image dan Price Terhadap Minat Beli Konsumen di Tiktok Shop Pada Mahasiswa Universitas PGRI Wiranegara - Sabiila, Nadya Faza; Sangadji, Etta Mamang; Indarti, Nunuk (E-Prosiding Seminar Nasional Manajemen dan Akuntansi STIE Semarang (SNMAS), 2024)
The rapid development of technology has influenced various fields, including E- commerce. Indonesia ranks first in the use of E-commerce services, with 88.1% of internet users. TikTok, initially a social media platform, began expanding into E- commerce by introducing TikTok Shop in April 2021. As TikTok Shop is a new application, several factors such as Celebrity Endorsement, Brand Image, and Price are needed to influence consumer buying interest. This study aims to determine whether there is a partial and simultaneous influence of celebrity endorsement, brand image, and price variables on the buying interest of PGRI Wiranegara University students in TikTok Shop. This research uses a quantitative approach with a population of 116 students from PGRI Wiranegara University, and a sample of 54 students was taken using the Proportional Sampling technique. The data collection method used was a questionnaire. Data analysis used multiple linear regression techniques. The results showed that: 1) there is a positive influence of celebrity endorsement on consumer buying interest in TikTok Shop with a t-value = 3.009 > t-table = 2.009 and a significance of 0.004, 2) there is a positive influence of brand image on consumer buying interest in TikTok Shop with a t-value = 5.415 > t-table = 2.009 and a significance of 0.000, and 3) there is a positive influence of price on consumer buying interest in TikTok Shop with a t-value = 4.205 > t-table = 2.009 and a significance of 0.000. Simultaneously, these three variables significantly influence consumer buying interest with an F-calculated value of 45.366 > F-table 2.786 and a significance result of 0.000 < 0.05.